KARAKTERISTIK DAN POLA PERGERAKAN PENDUDUK KAWASAN PINGGIRAN KOTA MAKASSAR - Khairul Sani Usman (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2020)
The development proces of urban activities, especially the population activities to live in the suburbs caused the Makassar’s suburbs was experienced a rapid development. Along to the increasing of development activities, then certainly it will as revival new population movement increase too in suburbs area to go to the City of Makassar and surrounding areas. This study describes how the characteristics and patterns movement in working, schooling and shopping of the suburbs populatin to go to the Makassar city and around areas.The research has conducted in suburbs area of Makassar City that is in Subdistrict Somba Opu (Gowa regency).The analysis methode that using is descriptive analysis to know chracteristic and pattern of working, schooling, and shopping by suburbs population in Makassar with using Matriks Asal Tujuan (MAT). Based on the result of analysis research found the the pattern of suburban population movement which show that the movement tendency in the internal-external pattern that is 62.16% of the working population and 70.18% of the shopping who is the higest purpose in Pannakkukang Sub-district, while the population movement for school activities only 29.50%. This indicates that in the fulfillment of work and expenditure activities, the population in the study area is still very dependent on Makassar City, whereas in the case of fulfillment of school activities the population is not too dependent on the city of Makassar.